Fresh properties of HPSCC containing SRA and expansive admixtures - Pilar,Ronaldo (2018)
ABSTRACT Shrinkage-reducing admixture (SRA) and expansive admixture (EXA) were used in high performance self-compacting concrete (HPSCC) to mitigate autogenous shrinkage. In order to evaluate the fresh properties of concretes, the rheological parameters were determined in a ICAR rheometer at 10, 25, 40, 60 and 90 min. The flow behavior of the mixtures was described by Bingham, Herschel-Bulkley, and modified Bingham models. Slump flow test, V-funnel test and J-Ring test were also carried out at 10 min. Slump flow test was performed also after 90 min of mixing. The test results showed that, at 10 minutes, all mixtures had similar performances, independently of the SRA and EXA contents. However, the slump flow test shows a reduction of up to 24% of its diameter at 90 min for mixtures with EXA. Mixtures with EXA revealed a gradual increase in dynamic yield stress with elapsed time. In contrast, concretes with SRA exhibited less variation in its rheological properties. Statistical analysis (ANOVA) showed that, regardless of the rheological model adopted, the admixture content was not a significant factor for the yield stress, while the type of admixture and the time of testing greatly influenced the concretes rheological response.